Difficulties Faced by Residents and Clues for Solutions: A Qualitative Study - Ozlem Mıdık MD, PhD; Meral Demirören MD; Zeynep Baykan MD (SAGE Publishing, 2024)
A complex healthcare system often leads to the high variety experiences among medical postgraduate students. This study aims to reveal the difficulties they face during postgraduate education, their consequences, and coping strategies. This is a phenomenological study conducted by using the maximum diversity strategy from purposive sampling methods. Semi-structured interviews were conducted with 10 medical residents from different disciplines, 7 step of thematic analysis was applied. The findings were presented under the headings of challenges, outcomes, and ways of coping in line with the research questions. The sub-themes within the "postgraduate medical education" theme were "learning-teaching processes, educators, educational program, interactions, assessment, and evaluation." The sub-themes in the "culture/climate" theme were "academic environment, disruptive behaviors, rules and procedures, and hierarchy." The difficulties experienced by residents in the "health system" theme were examined under the sub-themes of "health care team, health service delivery, payment for service, patients, and their relatives." The sub-themes in the "specialization" theme were "scope and practices of the specialty area" and "perception of the specialty area." The difficulties in the "time/period" theme were analyzed under (1) senior and (2) junior sub-themes. The consequences of difficulties were examined under the themes of "deterioration in well-being and perception of incompetence." Coping with the difficulties was categorized into individual efforts, not expend effort, and getting support themes. Individual efforts were examined under the sub-themes of "sharing difficulties, communication-interaction, being a problem solver, maintaining well-being, and socializing." Sub-themes of getting support were classified as institutional and psychological. It is necessary to understand the phenomenon of "residents" difficulties'. All parts involved in PGME, should be aware that residents are in early adulthood. They have to recognize internal structural constraints, distinguish between internal and external factors. Solutions should go beyond individual development, systematic design and support mechanisms should be established at both institutional and national levels.